Deciphering acoustic emission signals in drought stressed branches: the missing link between source and sensor - Vergeynst, Lidewei L.; Sause, Markus G. R.; Hamstad, Marvin A.; Steppe, Kathy (Frontiers in Plant Science, 2015)
When drought occurs in plants, acoustic emission signals can be detected, but the actual causes of these signals are still unknown. By analyzing the waveforms of the measured signals, it should however be possible to trace the characteristics of the acoustic emission source and get information about the underlying physiological processes. A problem encountered during this analysis is that the waveform changes significantly from source to sensor and lack of knowledge on wave propagation impedes research progress made in this field. We used finite element modeling and the well-known pencil lead break source to investigate wave propagation in a branch. A cylindrical rod of polyvinyl chloride was first used to identify the theoretical propagation modes. Two wave propagation modes could be distinguished and we used the finite element model to interpret their behavior in terms of source position for both the PVC rod and a wooden rod. Both wave propagation modes were also identified in drying-induced signals from woody branches, and we used the obtained insights to provide recommendations for further acoustic emission research in plant science.